United States, buildings along street in Ketchikan - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1934)
Buildings on hillside looking over city street. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3